Impact of Influencer Marketing on Apparel buying Behavior of Millennials - Nikita Gautam (International Journal of Advanced Science and Technology, 2020)
Definition of marketing has changed over time. Now, it’s not just a manner of promoting and spreading awareness about a brand, but it’s about giving a whole new experience to the customers. The number of people using mobile phones have increased rapidly and with that people spend a major part of the day surfing on their phones and using social media platforms. This has given a new medium to the brands to get into contact with individuals. Thus, the brands have been coming up with new strategies to gain customers attention and cope up with the increase in use of social media. The increasing trust between the influencers and the customers has compelled many organizations to increase their spending on a new approach known as influencer marketing. The trend of influencer marketing started with famous celebrities advertising the brands, but now with social media like Instagram and Tiktok, we have a new set of influencers, with millions of followers, who regularly post their everyday activities and videos. These influencers are considered to be the most authentic promotion channel to reach the customers. This paper aims to study the relation between the trust factor and perception of millennials about influencers with their intention of buying the promoted brand. To test the impact of influencers on millennial apparel purchasing behavior,